A kind of anti-flash rust sealant specially used for container and preparation method thereof

By using aqueous solutions of sodium nitrite and organic acid salt as the anti-flash rust agent compound solution in aqueous adhesives, the problem of flash rust in aqueous adhesives under high temperature and high humidity conditions is solved, and the resistance to yellowing is improved, and it is suitable for container sealants.

CN115895529BActive Publication Date: 2025-05-02GUANGZHOU JOINTAS CHEM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211514754.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2025-05-02
Estimated Expiration
2042-11-30

AI Technical Summary

Technical Problem

Existing water-based adhesives can easily cause flash rust of steel substrates under extremely high temperature and high humidity conditions, and commonly used anti-flash rust agents may affect the physical properties of the adhesive or cause yellowing.

Method used

A specific proportion of aqueous solution of sodium nitrite and organic acid salts (such as sodium benzoate) is used as a composite solution for anti-flash rust agents, and added to the acrylic emulsion to form a container-specific anti-flash rust sealant.

Benefits of technology

It significantly improves the anti-flash rust properties and yellowing resistance of the anti-flash rust sealant. It is suitable for sealants in containers without affecting the physical properties of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003971561310000091
    Figure BDA0003971561310000091
Patent Text Reader

Abstract

The present invention discloses a special anti-flash rust sealant for containers, comprising 30-55 parts of acrylic emulsion; 5-10 parts of plasticizer; 0.3-1.2 parts of emulsifier; 0.5-2 parts of coupling agent; 0.5-3 parts of antifreeze agent; 40-60 parts of filler; and 0.1-2 parts of anti-flash rust agent compound solution. In the sealant system of the present invention, a specific proportion of sodium nitrite and an aqueous solution of an organic acid salt and a derivative is selected as the anti-flash rust agent compound solution, which can greatly improve the anti-flash rust performance and anti-yellowing property of the anti-flash rust sealant, and is particularly suitable for the sealant for containers, which has a good anti-flash rust repair effect and does not affect or even improves the physical properties and anti-yellowing property of the original water-based adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of sealants, and particularly relates to an anti-flash rust sealant special for containers and a preparation method thereof. Background Art

[0002] The history of human use of adhesives can be traced back to a very long time ago, and its application in industry has a history of more than 200 years. The vigorous development of industry has also driven the advancement of adhesive technology. Adhesives can be seen in many fields such as construction, electronics, automobiles, and ships.

[0003] Harmful gases will be generated during the processing and production of adhesives, causing irreversible damage to the health of construction workers and polluting the environment. With the emphasis on "green and environmental protection" in many countries, relevant policies on green adhesives have also been released one after another. Therefore, the concept of low VOC, zero pollution adhesives has been highly praised, and it will definitely be one of the important directions for the future development of adhesives. Of course, the biggest difference between water-based adhesives and solvent-based adhesives is the choice of solvents. The biggest problem facing water-based adhesives is that when water is used as a solvent, it will cause corrosion to the substrate to a certain extent. Therefore, improving the corrosion resistance of water-based adhesives is the key to current development.

[0004] In the field of water-based adhesive anti-corrosion, it has always been an urgent problem to be solved in the development of industry. At the same time, there are many solutions. First, apply a primer on the steel surface, and then cover the surface of the paint with water-based adhesive. Although this can greatly reduce the flash rust problem, it is inevitable that the substrate flash rust will penetrate the surface of the paint, and then corrode the adhesive to a certain extent. Because the water contained in the water-based adhesive and water-based paint is one of the necessary conditions for flash rust on steel.

[0005] When the steel substrate is directly covered with water-based adhesive, under extremely high temperature and high humidity conditions, due to the high latent heat of volatilization of water, water stays on the surface of the steel for a long time, making the steel prone to rust. Water-based adhesives mainly use water as a solvent or dispersant, and the formation of flash rust is also related to the dispersion medium of the water-based adhesive. When the water-based adhesive is covered on the surface, a primary battery is formed between the steel surface and the water-based adhesive surface, and electrochemical corrosion occurs, thus forming the surface flash rust phenomenon after the water-based adhesive is cured.

[0006] In order to solve the technical problem under this extreme condition, water-based anti-flash rust agents were introduced and added to water-based adhesives, so that when the adhesive covers the steel surface, the formation of flash rust can be effectively prevented. This is because the anti-flash rust agent contains organic complexes and a variety of organic compounds, which can effectively organize the cathode chemical reaction on the steel surface, prevent the ionization of iron, and thus avoid the formation of flash rust. However, the anti-flash rust agents currently used have their own characteristics. The addition of some anti-flash rust agents will affect the physical properties of the original water-based adhesive and cause yellowing of the sealant. Summary of the invention

[0007] The purpose of the present invention is to provide a special anti-flash rust sealant for containers, which has good anti-flash rust repair effect and does not affect or even improves the physical properties and anti-yellowing performance of the original water-based adhesive.

[0008] Necessarily, the present invention also provides a method for preparing the above-mentioned anti-flash rust sealant for containers.

[0009] The technical solution of the present invention is:

[0010] A special anti-flash rust sealant for containers, comprising the following substances in parts by weight:

[0011] 30-55 parts of acrylic emulsion;

[0012] 5-10 parts of plasticizer;

[0013] Emulsifier 0.3-1.2 parts;

[0014] 0.5-2 parts of coupling agent;

[0015] 0.5-3 parts of antifreeze;

[0016] 40-60 parts of filler;

[0017] 0.1 to 2 parts of anti-flash rust agent compound solution.

[0018] The anti-flash rust agent composite solution is an aqueous solution of sodium nitrite and organic acid salts and derivatives, wherein the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of organic acid salts and derivatives in the aqueous solution is 40wt%.

[0019] Wherein, the organic acid salt and its derivatives are sodium benzoate.

[0020] Wherein, the acrylic emulsion is prepared by the following method:

[0021] 45-60 parts by weight of deionized water, 13-15 parts by weight of acrylate, 14-17 parts by weight of isooctyl acrylate, 7-12 parts by weight of styrene, 20-40 parts by weight of ethylene glycol dimethacrylate, and 0.5-2 parts by weight of emulsifier are sequentially added into a reaction kettle, and emulsified for 40-50 minutes to prepare an emulsion;

[0022] The initiator and deionized water mixture is added dropwise twice: the first time, 0.5-1 parts by weight of the initiator and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of the emulsifier are mixed with the previously prepared emulsion, and the initiator is slowly added dropwise when the system temperature is raised to 80-85°C, and the reaction is kept warm for 1-1.5 hours; the second time, 0.5-2 parts by weight of the initiator and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90°C and slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50°C, and a pH adjuster is added to adjust the pH value of the reaction system to between 7-8, and an acrylic emulsion can be obtained. Wherein, the initiator for preparing the acrylic emulsion is selected from one or more of sodium persulfate, potassium persulfate, and ammonium persulfate;

[0023] Sodium lauryl sulfate is used as an emulsifier for preparing the acrylic emulsion;

[0024] The pH regulator for preparing the acrylic emulsion is triethanolamine.

[0025] Wherein, the plasticizer is dioctyl phthalate or dibutyl phthalate.

[0026] Among them, the emulsifier is preferably a fatty alcohol polyoxyethylene ether non-ionic emulsifier.

[0027] Wherein, the coupling agent is a titanate coupling agent.

[0028] Wherein, the antifreeze agent is selected from ethylene glycol or 1,2-propylene glycol.

[0029] Wherein, the filler is selected from heavy calcium carbonate, talcum powder or kaolin, and the mesh number is 600-1400 mesh.

[0030] A method for preparing the above-mentioned special anti-flash rust sealant for containers comprises the following steps:

[0031] Mix the acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution in proportion, stir thoroughly and store in a sealed container at room temperature.

[0032] Compared with the prior art, the present invention provides a special anti-flash rust sealant for containers, including 30-55 parts of acrylic emulsion; 5-10 parts of plasticizer; 0.3-1.2 parts of emulsifier; 0.5-2 parts of coupling agent; 0.5-3 parts of antifreeze agent; 40-60 parts of filler; and 0.1-2 parts of anti-flash rust agent compound solution. In the sealant system described in the present invention, an aqueous solution of sodium nitrite and an organic acid salt and its derivatives in a specific proportion is selected as the anti-flash rust agent compound solution. Sodium nitrite is an inorganic salt that mainly reacts with the metal surface to form a passivation film to protect the metal. However, due to its own structure, it is easily decomposed under long-term ultraviolet irradiation, resulting in yellowing of the colloid. Therefore, it is considered to compound the anti-flash rust agent and add the organic acid salt sodium benzoate. The organic anti-flash rust agent can form an adsorption film with the metal surface, thereby isolating the metal surface and inhibiting the decomposition of nitrite. The anti-flash rust performance and anti-yellowing property of the anti-flash rust sealant can be greatly improved. The sealant is particularly suitable for containers, has a good anti-flash rust repair effect, does not affect or even improves the physical properties and anti-yellowing property of the original water-based adhesive. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with specific implementation methods.

[0034] Sources of substances in Examples and Comparative Examples:

[0035] Acrylic emulsion: Homemade.

[0036] Plasticizer: Dioctyl phthalate, Jinan Xinchaorui Chemical Co., Ltd., Model 00123

[0037] Emulsifier: Fatty alcohol polyoxyethylene ether non-ionic, Guangdong Jinlong Chemical Import and Export Co., Ltd., Model: AEO-7

[0038] Coupling agent: titanate coupling agent, Dongguan Kangjin New Material Technology Co., Ltd., model: NDZ-201;

[0039] Antifreeze: ethylene glycol, commercially available;

[0040] Filler: heavy calcium carbonate, 600-1400 mesh, Lingshou County Qiangdong Mineral Products Processing Plant, model: qd-908;

[0041] Organic acid salt: sodium benzoate, commercially available;

[0042] Sodium nitrite: powdered, commercially available.

[0043] The remaining raw materials were commercially available.

[0044] Example 1

[0045] Preparation of acrylic emulsion:

[0046] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0047] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0048] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0049] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and sodium benzoate, the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of sodium benzoate in the aqueous solution is 40wt%.

[0050] Example 2

[0051] Preparation of acrylic emulsion:

[0052] 45 parts by weight of deionized water, 13 parts by weight of acrylate, 14 parts by weight of isooctyl acrylate, 7 parts by weight of styrene, 20 parts by weight of ethylene glycol dimethacrylate, and 0.5 parts by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 50 minutes to prepare an emulsion;

[0053] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0054] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0055] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and sodium benzoate, the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of sodium benzoate in the aqueous solution is 40wt%.

[0056] Example 3

[0057] Preparation of acrylic emulsion:

[0058] 60 parts by weight of deionized water, 15 parts by weight of acrylate, 17 parts by weight of isooctyl acrylate, 12 parts by weight of styrene, 40 parts by weight of ethylene glycol dimethacrylate, and 2 parts by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 40 minutes to prepare an emulsion;

[0059] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0060] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0061] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and sodium benzoate, the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of sodium benzoate in the aqueous solution is 40wt%.

[0062] Comparative Example 1

[0063] Preparation of acrylic emulsion:

[0064] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0065] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0066] Acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after being fully stirred;

[0067] Among them, the anti-flash rust agent is powdered sodium nitrite which is directly added in proportion.

[0068] Comparative Example 2

[0069] Preparation of acrylic emulsion:

[0070] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0071] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0072] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after being fully stirred;

[0073] The anti-flash rust agent solution is an aqueous solution of sodium benzoate, and the mass fraction of the organic acid salt and its derivatives in the aqueous solution is 44.4wt%.

[0074] Comparative Example 3

[0075] Preparation of acrylic emulsion:

[0076] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0077] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0078] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0079] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and organic acid amine (dimethylethanolamine), the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of the organic acid amine in the aqueous solution is 40wt%.

[0080] Comparative Example 4

[0081] Preparation of acrylic emulsion:

[0082] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0083] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0084] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0085] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and sodium benzoate, the mass fraction of sodium nitrite in the aqueous solution is 7wt%, and the mass fraction of organic acid salts and derivatives in the aqueous solution is 28wt%.

[0086] Comparative Example 5

[0087] Preparation of acrylic emulsion:

[0088] 55 parts by weight of deionized water, 14 parts by weight of acrylate, 15 parts by weight of isooctyl acrylate, 10 parts by weight of styrene, 30 parts by weight of ethylene glycol dimethacrylate, and 1 part by weight of sodium lauryl sulfate were sequentially added into a reaction kettle and emulsified for 45 minutes to prepare an emulsion;

[0089] The sodium persulfate and deionized water mixture is added dropwise twice: firstly, 0.5-1 parts by weight of sodium persulfate and 3-6 parts by weight of deionized water are dissolved and mixed, and then 0.5-1.5 parts by weight of sodium dodecyl sulfate is mixed with the previously prepared emulsion, and the sodium persulfate is slowly added dropwise when the system temperature is raised to 80-85° C., and the reaction is kept warm for 1-1.5 hours; secondly, 0.5-2 parts by weight of sodium persulfate and 5-7 parts by weight of deionized water are dissolved and mixed, and the system temperature is raised to 85-90° C. and the addition is slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50° C., triethanolamine is added to adjust the pH value of the reaction system to between 7 and 8, and an acrylic emulsion can be obtained.

[0090] The acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution were mixed according to the weight parts shown in Table 1, and sealed and stored at room temperature after sufficient stirring;

[0091] The anti-flash rust agent compound solution is an aqueous solution of sodium nitrite and sodium benzoate, the mass fraction of sodium nitrite in the aqueous solution is 3wt%, and the mass fraction of organic acid salts and derivatives in the aqueous solution is 12wt%.

[0092] Table 1 Materials used in Examples and Comparative Examples (Unit: parts by weight)

[0093] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Acrylic Emulsion 40.65 38.15 38.15 40.65 40.65 40.65 40.65 40.65 Plasticizers 6.12 7.55 6.35 6.12 6.12 6.12 6.12 6.12 Emulsifier 0.5 0.8 1 0.5 0.5 0.5 0.5 0.5 Coupling agent 0.5 0.8 1 0.5 0.5 0.5 0.5 0.5 antifreeze 0.5 0.8 1 0.5 0.5 0.5 0.5 0.5 filler 51.23 51.2 51.5 51.23 51.23 51.23 51.23 51.23 Anti-flash rust agent compound solution / anti-flash rust agent 0.5 0.7 1 0.5 0.5 0.5 0.5 0.5

[0094] The sealants prepared in the examples and comparative examples are applied to the container paint board. When in use, the prepared and sealed water-based container acrylic anti-corrosion adhesive is directly applied to the container paint board and cured at room temperature.

[0095] Then the flash rust resistance and yellowing resistance were tested, and the test results are listed in Table 2.

[0096] 1. Color: visual inspection

[0097] 2. Sag: Test the vertical sag and horizontal sag of the sealant according to the test standard GB / T 13477.6-2002;

[0098] 3. Consistency: The consistency of the sealant is tested according to the test standard GB 1749-79 (89);

[0099] 4. Surface drying time: tested according to the testing standard GB / T 13477.6-2002;

[0100] 5. Low temperature flexibility: tested according to the testing standard GB / T 13477.7-2002;

[0101] 6. Peeling adhesion: Test the peeling strength and bonding damage area according to the testing standard GB / T 13477.18-2002;

[0102] 7. Flash rust resistance: After the sample is prepared, observe it for 7 days at a temperature of (50±2)℃ and a relative humidity of (50±5)%, and record the status on the 3rd, 5th and 7th days respectively;

[0103] 8. Anti-yellowing property: Put the sample into the anti-yellowing box (distance between turntable and light source: 250mm, 300W bulb, temperature 50℃), test for 3 hours, take it out and compare it with the original sample, and compare it with the sample without anti-yellowing (white) by visual inspection. If there is color difference, it means yellowing, and if there is no color difference, there is no abnormality.

[0104] Table 2 Performance test table of the sealants obtained in the embodiments and comparative examples

[0105]

[0106] The data show that the container-specific anti-flash rust sealant of the present invention uses an aqueous solution of sodium nitrite and organic acid salts and derivatives in a specific ratio as the anti-flash rust agent compound solution, which can greatly improve the anti-flash rust performance and anti-yellowing properties of the anti-flash rust sealant, and is particularly suitable for use as a sealant for containers.

[0107] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A special anti-flash rust sealant for containers, characterized in that The following substances are included in parts by weight: 30-55 parts of acrylic emulsion; 5-10 parts of plasticizer; Emulsifier 0.3-1.2 parts; 0.5-2 parts of coupling agent; 0.5-3 parts of antifreeze; 40-60 parts of filler; 0.1 to 2 parts of anti-flash rust agent compound solution; The anti-flash rust agent composite solution is an aqueous solution of sodium nitrite and sodium benzoate, wherein the mass fraction of sodium nitrite in the aqueous solution is 10wt%, and the mass fraction of sodium benzoate in the aqueous solution is 40wt%; The acrylic emulsion is prepared by the following method: 45-60 parts by weight of deionized water, 13-15 parts by weight of acrylate, 14-17 parts by weight of isooctyl acrylate, 7-12 parts by weight of styrene, 20-40 parts by weight of ethylene glycol dimethacrylate, and 0.5-2 parts by weight of emulsifier are sequentially added into a reaction kettle, and emulsified for 40-50 minutes to prepare an emulsion; The initiator and deionized water mixture is added dropwise twice: the first time, 0.5-1 weight part of initiator and 3-6 weight parts of deionized water are dissolved and mixed, and then 0.5-1.5 weight parts of emulsifier are mixed with the previously prepared emulsion, and the initiator is slowly added dropwise when the system temperature is raised to 80-85°C, and the reaction is kept warm for 1-1.5 hours; the second time, 0.5-2 weight parts of initiator and 5-7 weight parts of deionized water are dissolved and mixed, and the system temperature is raised to 85-90°C and slowly added dropwise, and the addition is completed within 3-4 hours, and then the reaction is kept warm for 1-2 hours; finally, the temperature is lowered to 40-50°C, and a pH adjuster is added to adjust the pH value of the reaction system to between 7 and 8, so as to obtain an acrylic emulsion.

2. The container-specific anti-flash rust sealant according to claim 1, characterized in that: The initiator for preparing the acrylic emulsion is selected from one or more of sodium persulfate, potassium persulfate and ammonium persulfate; The emulsifier used to prepare the acrylic emulsion is sodium lauryl sulfate; The pH regulator for preparing the acrylic emulsion is triethanolamine.

3. The container-specific anti-flash rust sealant according to claim 1, characterized in that: The plasticizer is dioctyl phthalate or dibutyl phthalate.

4. The container-specific anti-flash rust sealant according to claim 1, characterized in that: The emulsifier used is fatty alcohol polyoxyethylene ether nonionic emulsifier.

5. The container-specific anti-flash rust sealant according to claim 1, characterized in that: The coupling agent is a titanate coupling agent.

6. The anti-flash rust sealant for containers according to claim 1, characterized in that: The antifreeze agent is selected from ethylene glycol or 1,2-propylene glycol.

7. The anti-flash rust sealant for containers according to claim 1, characterized in that: The filler is selected from heavy calcium carbonate, talc or kaolin, and has a mesh size of 600-1400 meshes.

8. A method for preparing the anti-flash rust sealant for containers as claimed in any one of claims 1 to 7, characterized in that The following steps are involved: Mix the acrylic emulsion, plasticizer, emulsifier, coupling agent, antifreeze agent, filler and anti-flash rust agent compound solution in proportion, stir thoroughly and store in a sealed container at room temperature.

Citation Information

Patent Citations

  • Environment-friendly aqueous sealant for container

    CN101967256A

  • Submerged arc welding flash rust resistant water-based acrylic acid anticorrosive primer and preparation method thereof

    CN114058232A